PLAN-DO-CHECK-ACTION (PDCA) BASED APPROACH TO REDUCE MACHINE DOWNTIME BY PROPOSING DESIGN OF MACHINE COMPONENT: THE CASE OF A BOTTLED WATER COMPANY - Raodah; Amar, Kifayah; Rusman, Muhammad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
The purpose of this paper is to report on the application of the PDCA cycle in reducing machine downtime of bottled water production in an Indonesian manufacturing company. The PDCA cycle was used as a methodology in this study to solve machine downtime problems. During brainstorming sessions with the company’s representative, tools such as 5W+1H and the fishbone diagram were used. The collected data was then used to design a machine component prototype in order to reduce downtime. The main result of this study was the design of a machine component to help reduce machine downtime by adding it to the cap-sealing machine. Based on observations over three months, the assembled component reduced downtime from 31.37% to 8.63%, exceeding the company’s standard of a maximum loss of 10%. Furthermore, the company will benefit from this research because the designed machine component will reduce machine downtime and successfully increase the company’s KPI value.